Auditor’s duty to blow the whistle – Recent developments in Finland - Reiman, Lauri-Heikki (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis analyzes auditors’ reporting duty to public authorities. It studies auditors’ reporting duties in Swedish Companies Act, Finnish government’s proposals HE 212/2014 and HE 254/2014 and EU Regulation 537/2014. The objective of this paper is to analyze whether financial crime prevention activities, such as the auditors’ reporting duty, should be considered as a part of auditors’ duties. In addition, this paper analyzes how the reporting duties are justified in preliminary works of passed legislation and legal literature. This paper also analyzes what kind of impact reporting duties have in auditor’s role. The paper’s methodology is legal dogmatics and also legal comparison is made between above mentioned legal norms. When I assess the Finnish government proposals and the Swedish reporting duty, the perspective is partly legal politics. Auditor’s active reporting duty to authorities is internationally understood as whistle-blowing. Its significance has increased especially after financial scandals. As a result there have been public ambitions to incorporate auditors more closely in the fight against financial crime. However, auditing is not an authoritative position but a position of trust, where auditors primarily work on behalf of company shareholders by monitoring their investment. Besides this, auditing also has a wider societal role in securing the correctness of financial information. Auditors’ whistle-blowing duties may be perceived as a response to the failure of the state to develop adequate public crime prevention mechanisms for corporations. For auditing profession whistle-blowing duties can be seen as problematic, especially due to the profession’s own ethical principles. As stated in the paper, the whistle-blowing duties require auditors to breach their client confidentiality obligation and thus harm auditors’ position as an independent party. Auditor’s independence and client confidentiality are central axioms for plausible auditing. However, these principles are not absolute and they yield when an important public interest is at stake. The paper shows that auditor’s whistle-blowing duties are problematic as they increase the audit risk and thus the audit fees. Such duties also obscure auditor’s main task and do not necessarily reach the most flagrant cases. A general whistle-blowing duty is problematic for both auditors’ and audited companies’ legal security. Although auditors conduct legality surveillance, this paper concludes that auditor’s reporting duties to authorities should be limited to exceptions. General rules should be avoided.